2020
DOI: 10.14198/jhse.2021.162.08
|View full text |Cite
|
Sign up to set email alerts
|

Current trends of the serve skill in relation to the in-game roles of the elite volleyball players: Comparison between genders

Abstract: The aim of this study was to investigate the current trends of the serve skill for each one of the in-game roles of the players for both genders in high-level volleyball. The serve actions of male (M) and female (F) elite players from 20 volleyball games (M = 10, F = 10) of the final phase World League 2018 were assessed. The analysed variables were comprised of the serve type, the serving area (SA), the serve direction, the in-game role of the server and the serve performance. Results showed that men mainly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…22 The highest percentage of jump serves used by men (75%) compared with women (4.9%) could explain this significant difference. 44 On the contrary, with serve for 5-set marches, 2.5 more points in block or a + 1.2% increase of block per point percentage in winners compared with losers, increases the probability of winning a match. Despite the lower correct classification in 5-set compared with 3-set and 4-set matches, winners differ significantly (P < .05) mostly due to their higher blocking skill values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The highest percentage of jump serves used by men (75%) compared with women (4.9%) could explain this significant difference. 44 On the contrary, with serve for 5-set marches, 2.5 more points in block or a + 1.2% increase of block per point percentage in winners compared with losers, increases the probability of winning a match. Despite the lower correct classification in 5-set compared with 3-set and 4-set matches, winners differ significantly (P < .05) mostly due to their higher blocking skill values.…”
Section: Discussionmentioning
confidence: 99%
“…22 The highest percentage of jump serves used by men (75%) compared with women (4.9%) could explain this significant difference. 44…”
Section: Discussionmentioning
confidence: 99%
“…Tili et al [47], Wnorowski et al [48] investigated the anthropometric data of the winners of games under the aegis of the FIVB before and after changes in the rules of the game and depending on the specialization. Other studies [49,50] have shown the effectiveness of setting the ball to qualified volleyball players in competitive conditions. Such approaches are focused on supporting coaches and players to develop game strategies, exercise planning.…”
Section: Original Articlementioning
confidence: 99%
“…approach should be used in the training of volleyball students. Barzouka et al [22] investigated current trends in serve skills for each of the high-level volleyball players' roles. The authors evaluated the actions of elite players in 20 volleyball matches of the final phase of the 2018 World League.…”
mentioning
confidence: 99%